PENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA MATERI SIFAT-SIFAT CAHAYA MELALUI MODEL PEMBELAJARAN VISUAL AUDITORI KINETIK (VAK) PADA SISWA KELAS V SD NEGERI REMBES 02 KECAMATAN BRINGIN KABUPATEN SEMARANG TAHUN PELAJARAN 2016/2017 - Harsiti Harsiti (Universitas Ngudi Waluyo, 2020)
This research is an effort to improve student learning outcomes in the material properties of light in science subjects through the Kinesthetic Virtual Auditory learning model (VAK). Classroom action research was carried out on fifth grade students of SD Negeri Rembes 02, Bringin District, Semarang Regency, 2016/2017 academic year. This research was motivated by the learning outcomes of many students who were still below the KKM in science lessons, of the 24 students who scored the Minimum Completeness Criteria were 10 students or 41.67%. The improvement of learning outcomes can be seen from the results of classroom action research in cycles I and II. In the first cycle students who completed with the minimum completeness criteria were 16 students or 66.67%. In cycle II students who completed with KKM 70 were 21 students or 87.5%, an increase of 20.83% from cycle I. While the student activity process also increased, where in cycle I only reached 67% or 16 students reached classical ketutansan. But in cycle II there was a very significant increase reaching 92% or 22 students played an active role in participating in the learning process.